PELAYANAN KESEHATAN LANJUT USIA DI WILAYAH KERJA PUSKESMAS I DENPASAR SELATAN - I.G P.S. Aryana; R. A.T. Kuswardhani; I. N. Astika; I. B.P. Putrawan; N. K.R. Purnami; A. A.M.P. Triningrat; I.D. G.A.E. Putra; N. K.S. Diniari; K. Widyastuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The number of elderly reached 6146 elderly (23.44% of the total population) in South Denpasar sub-district. The complexity of the health problems experienced by the elderly and the special character possessed by the elderly, it is necessary to use a different method and approach by conducting a comprehensive health examination (bio-psycho-social aspect) which aims to provide an understanding for the elderly to their own health and improve their abilities and abilities. the role of family and community in overcoming the health of the elderly. The activities carried out include health services for the elderly with a comprehensive health examination including a plenary assessment of geriatric patients (P3G), physical examination, eyes, ENT, mental and nervous health). Community service is carried out for the elderly in Sesetan Village, South Denpasar. There are 130 seniors who participated in this service. The elderly with the age group 60 - 69 years amounted to 72 people (55.4%) who attended the most health services. 44 men (33.8%) and 86 people (66.2%) were female. The results of the examination showed that 75 people (57.7%) were suffering from infectious diseases, 8 people (6.2%) were malnourished, 49 people (37.7%) were obese, and 25 people (19.2%) had sarcopenia. (loss of muscle mass). Based on the results of the elderly health examination, this elderly health service activity is expected to provide benefits to the elderly and their families. Keywords: Elderly, medical examination, comprehensive, family role, quality of lif